Revolutionising Security Operations in the BFSI Sector with XDR Technology - Rehman, Fahad (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
This research intends to examine the effectiveness of Extended Detection and Response (XDR) technology in altering Security Operations Centres (SOCs) within the Banking, Financial Services, and Insurance (BFSI) sector. The study addresses the rising issue of increasing cyber threats, which require a more integrated and flexible approach to security. By analysing the current state of cybersecurity in the BFSI sector, it will be necessary to pinpoint both the weaknesses in existing systems and the specific areas where XDR can provide significant enhancements. To address this issue correctly, data on response times to incidents, rates of threat detection, and system performance post-XDR implementation is needed. Additionally, the context provided by feedback from industry experts on operational advancements and challenges is essential, as it enables a more comprehensive comprehension of the manner in which XDR is integrated into the broader cybersecurity strategies of the BFSI sector. This paper implements a mixed-method approach that integrates secondary data collection methodologies. This research study analyses how Extended Detection and Response (XDR) technology improves security operations in the Banking, Financial Services, and Insurance (BFSI) business as cyber threats increase and traditional security solutions become ineffective. The study employs a mixed-methods approach with secondary data collection, gathering numerical data on incident response times and financial impacts, along with qualitative insights from industry reports and previous case studies highlighting customer success stories shared by cybersecurity experts. The findings show that organisations using XDR technologies saw a notable drop in response times and a significant reduction in the financial and operational damages of breaches compared to traditional security setups. These findings illustrate XDR’s game-changing capacity to improve situational awareness, streamline incident responses, and strengthen overall cybersecurity in the BFSI industry. The significance of this research extends beyond financial organisations, providing a vital foundation for understanding the changing nature of cyber dangers important to any industry dealing with sensitive data. Furthermore, the effects of adopting XDR technology are seen in the broader cybersecurity area, serving as a roadmap for enterprises wishing to upgrade their security procedures in a more complex threat scenario.